The Southern Palestine Bedouin between Colonialism and Nationalism: Comparing Representations in British Mandatory Documents and Palestinian Newspapers, 1930-1948 - Nasasra, Mansour (Journal of Holy Land and Palestine Studies, 2016)
Based on British archival documents and Palestinian newspapers from the 1930s, the paper draws some conclusions on the representation of the Beersheba (Bir al-Sabi') Bedouinin both British colonial discourse and in the press and voices of Palestinian nationalism. By reviewing British archival documents, including private diaries of British officers, I argue that the British colonial authorities developed strategies and practices to rule the Beersheba Bedouin as a group separate and disconnected from the rest of the Palestinian communities in Mandate Palestine. This contrasts with the Palestinian newspapersal-Difa', Falastin, Huna al-Quds, al Carmelthat from the 1930s and 1940s presented the Bedouin as an active agent in the Palestinian body politic, participating in numerous outlets, such as in the Higher Arab Committee, the Higher Islamic Council in Jerusalem and Gaza, as well as in Palestinian conferences.